Yield and Grain Protein Content of Aromatic Boro Rice (cv. BRRI dhan50) as Influenced by Integrated Fertilizer and Weed Management - Roy, P.; Sarkar, M.A.R.; Paul, S.K. (International Journal of Applied Sciences and Biotechnology, 2017)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during December 2014 to May 2015 to study the effect of integrated fertilizer and weed management on the yield and gain protein content of aromatic Boro rice (cv. BRRI dhan50). The experiment comprised six sets of fertilizer managements. 1. Negative control having no fertilizers and no manures, 2. Recommended dose of inorganic fertilizers (i.e. Urea, TSP, MoP, Gypsum, ZnSO4 @ 250, 120, 120, 100, 10 kg ha-1, respectively), 3. 50% of recommended dose of inorganic fertilizers + cowdung @ 5 t ha-1, 4. 75% of recommended dose of inorganic fertilizers + cowdung @ 5 t ha-1, 5. 50% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1, 6. 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1. Four weed managements 1. Control (no weeding), pre-emergence herbicide, 2. Panida 33 EC + one hand weeding at 35 DAT, 3. Post-emergence herbicide, Granite 240 SC + one hand weeding at 35 DAT and 4. Pre-emergence herbicide, Panida 33 EC + post-emergence herbicide, Granite 240 SC. The highest grain yield (6.40 t ha-1), grain protein content (7.79%) and benefit cost ratio (2.20) were obtained from 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1 with pre-emergence herbicide, Panida 33 EC @ 2.5 l ha-1 + post-emergence herbicide, Granite 240 SC @ 93.70 ml ha-1 while their corresponding lowest values were found inweedy check without fertilization. Weed infestation reduced 58.28% grain yield in control plots due to crop-weed competition compared to plot receiving pre-emergence herbicide + post-emergence herbicide. It can be concluded that 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1 combined with pre-emergence herbicide, Panida 33 EC @ 2.5 l ha-1 + post-emergence herbicide, Granite 240 SC @ 93.70 ml ha-1 may be used to obtain the highest grain yield and grain protein content of aromatic Boro rice (cv. BRRI dhan50). Int. J. Appl. Sci. Biotechnol. Vol 5(1): 51-58